TINJAUAN ‘URF TERHADAP BUDAYA EKONOMI DALAM USAHA FOTOKOPI PERANTAU MINANGKABAU DI YOGYAKARTA - Mahlil Bunaiya; Delvy Hamzah; Mawaddatul Ulfa (Institut Agama Islam Negeri Batusangkar, 2021)
One of the efforts to meet the needs of the Minangkabau people that they achieve is through migration, as in the economic culture of Minangkabau immigrants from Nagari Atar Batusangkar, Padang Gantiang District, Tanah Datar Regency. About 99% of the imigrants were found in the field involved in Photo Copying businesses scattered in the city of Yogyakarta. The hope is that people's behavior in fulfilling the economy can continue to run well and in accordance with Islamic law. This study aims to explain how Urf's review of the economic culture of Minangkabau migrants in Yogyakarta using a qualitative descriptive research methodology. The results of the study conclude several things, among others: First, according to records in 2015 the number of Minangkabau residents in Yogyakarta reached 10,000 people or around 350 families, and those who run photocopy businesses are 80 families or 155 tablets. Second, the Economic Culture in the photocopy of the Minangkabu Community in Yogyakarta is referred to as 'Urf in Islamic law, because it fulfills several conditions' Urf and the law is mubah. Third, related to economic culture can furthermore be one of the studies that offers siding to the local community's economy which has basically been an economic support since the past in an effort to promote life, as well as' Urf which can then be used as a method and source of Islamic law in its development. economy because it conforms to Islamic principles.